Circular Microstrip Antennas in 5G: Evaluating Metamaterial Integration - Israel Adeolu Oluwafemi; Ubong Ukommi; Emmanuel Ubom; Akanniyene Obot (ABUAD Journal of Engineering Research and Development)
The rapid emergence of Fifth-Generation (5G) technologies necessitate the development of highly efficient antenna systems with compact design that can support Ultra-Wideband (UWB) frequencies. This work presents the design and enhancement of a Circular Microstrip Antenna (CMSA) for 5G UWB applications using metamaterials. The study focuses on the design of CMSA and the integration of a Complementary Split-Ring Resonator (CSRR) into the circular patch of the CMSA. The design is simulated using Computer Simulation Technology (CST) Studio 2023. The system design without metamaterials achieved a gain of 5.28 dBi and a bandwidth of 353.0 MHz. The integration of the CSRR led to an improvement in gain, 5.39 dBi at 3.8 GHz, which is above most of the literature reviewed, although there was a slight reduction in bandwidth to 135.2 MHz. The objectives of achieving a CMSA design with a gain between 5 to 10 dBi while maintaining a compact size were accomplished. Despite the slight reduction in bandwidth observed when integrating the CSRR into the CMSA, the overall results highlight the significant role metamaterials played in enhancing the performance of microstrip antennas for 5G technology applications.